Project Management from Simple to Complex - Open Textbook Library (Open Textbook Library, 2016)
In a world that is becoming more virtual, more global, and more complex, the project manager's ability to function in this environment becomes critical to the success of the project. Project Management from Simple to Complex explores project management within this complex, virtual, and global environment. This is not a standard textbook that was adapted to the new publishing paradigm; it was designed from the beginning to utilize its capabilities. The book is written in collaboration by an expert in Project Management and an expert in writing instructional textbooks and using technology for communicating online to create a unique learning environment that prepares students to manage projects in a global, multicultural, and online environment. Project Management from Simple to Complex features a new model for managing projects, as well as, exploration into the personal dynamics of project management and the role those dynamics play in project outcomes.
Chapter 1: Introduction to Project Management -- Chapter 2: Project Profiling -- Chapter 3: Project Phases and Organization -- Chapter 4: Understanding and Meeting Client Expectations -- Chapter 5: Working with People on Projects -- Chapter 6: Communication Technologies -- Chapter 7: Starting a Project -- Chapter 8: Project Time Management -- Chapter 9: Estimating and Managing Costs -- Chapter 10: Managing Project Quality -- Chapter 11: Managing Project Risk -- Chapter 12: Project Procurement and Closure
In English.
Description based on print resource
Keywords: Business -- Textbooks; Management -- Textbooks